1992
DOI: 10.1128/mcb.12.7.3305
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein kinase C in T-cell antigen receptor regulation of p21ras: evidence that two p21ras regulatory pathways coexist in T cells.

Abstract: T-lymphocyte activation via the antigen receptor complex (TCR) results in accumulation of p2l1 in the active GTP-bound state. Stimulation of protein kinase C (PKC) can also activate p2l'as, and it has been proposed that the TCR effect on p21r' occurs as a consequence of TCR regulation of PKC. To test the role of PKC in TCR regulation of p2l', a permeabilized cell system was used to examine TCR regulation of p2l1 under conditions in which TCR activation of PKC was blocked, first by using a PKC pseudosubstrate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(85 citation statements)
references
References 27 publications
3
82
0
Order By: Relevance
“…In other systems, signaling through G i2 proteins and tyrosine kinases converge on the MAP kinase (ERK) activation pathway, possibly at the level of Shc or Grb2 via tyrosine kinases of the Src family [7,8]. Thus, the ERK pathway, which, along with Src kinases Lck and Fyn, must be activated for TCR-induced IL-2 production [9,41,42], could be the pathway regulated by G i2 proteins in T lymphocytes. In summary, we have shown that in human T cells, G i2 proteins are required to modulate metabolic pathways leading to CD25/CD69 up-regulation, IL-2 production, and cell proliferation in response to TCR activation.…”
Section: Discussionmentioning
confidence: 99%
“…In other systems, signaling through G i2 proteins and tyrosine kinases converge on the MAP kinase (ERK) activation pathway, possibly at the level of Shc or Grb2 via tyrosine kinases of the Src family [7,8]. Thus, the ERK pathway, which, along with Src kinases Lck and Fyn, must be activated for TCR-induced IL-2 production [9,41,42], could be the pathway regulated by G i2 proteins in T lymphocytes. In summary, we have shown that in human T cells, G i2 proteins are required to modulate metabolic pathways leading to CD25/CD69 up-regulation, IL-2 production, and cell proliferation in response to TCR activation.…”
Section: Discussionmentioning
confidence: 99%
“…This leaves open the possibility that a GEF other than Sos is responsible for at least some of the Ras activation stimulated by antigen receptors. Part of the Ras activation stimulated by the T-cell receptor may also be due to Ras GAP inhibition rather than GEF activation (17,35). Lymphocytes have a Ras activation pathway that is initiated by phorbol ester treatment, and this is only partially or not at all dependent on tyrosine kinase activity (17,35).…”
Section: Discussionmentioning
confidence: 99%
“…Part of the Ras activation stimulated by the T-cell receptor may also be due to Ras GAP inhibition rather than GEF activation (17,35). Lymphocytes have a Ras activation pathway that is initiated by phorbol ester treatment, and this is only partially or not at all dependent on tyrosine kinase activity (17,35). Most of this phorbol ester-stimulated activation of Ras seems to be mediated by PKCs (35), but it is certainly possible that Ras-GRP could also contribute, perhaps with a dependence on concurrent PKC activity.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine phosphorylation of the TCR complex occurs within amino acid sequences known as immunoreceptor-based tyrosine activation motifs (ITAMs) and is required for receptor signaling function (4 -6). Activation of downstream signaling pathways, including the Ras/mitogen-activated protein kinase (MAPK) pathway, the phosphatidylinositol (PIP 2 ) pathway, and the phosphatidylinositol 3-kinase (PI-3-K) pathway, is dependent upon proteintyrosine kinase function (7)(8)(9)(10). However, the mechanisms by which the induction of tyrosine kinase activity initiates these diverse signaling processes is unknown.…”
Section: Activation Of T-lymphocytes Is Initiated By Engagement Of Thmentioning
confidence: 99%